A Comparative Study on the Oxidation of Label-Free Silver Triangular Nanoplates by Peroxides: Main Effects and Sensing Applications - Aleksei Furletov; Vladimir Apyari; Alexey Garshev; Stanislava Dmitrienko (Sensors, 2020)
Nowadays, analytical systems based on silver triangular nanoplates (AgTNPs) have been shown as good prospects for chemical sensing. However, they still remain relatively poorly studied as colorimetric probes for sensing various classes of compounds. This study shows that these nanoparticles are capable of being oxidized by peroxides, including both hydrogen peroxide and its organic derivatives. The oxidation was found to result in a decrease in the AgTNPs’ local surface plasmon resonance band intensity at 620 nm. This was proposed for peroxide-sensitive spectrophotometric determination. Five peroxides differing in their structure and number of functional groups were tested. Three of them easily oxidized AgTNPs. The effects of a structure of analytes and main exterior factors on the oxidation are discussed. The detection limits of peroxides in the selected conditions increased in the series peracetic acid < hydrogen peroxide < tert-butyl hydroperoxide, coming to 0.08, 1.6 and 24 μmol L−1, respectively. tert-Butyl peroxybenzoate and di-tert-butyl peroxide were found to have no effect on the spectral characteristics of AgTNPs. By the example of hydrogen peroxide, it was found that the determination does not interfere with 100–4000-fold quantities of common inorganic ions. The proposed approach was successfully applied to the analysis of drugs, cosmetics and model mixtures.